Characteristics of one-port surface acoustic wave resonator fabricated on ZnO/6H-SiC layered structure. (16th March 2018) - Li, Qi; Qian, Lirong; Fu, Sulei; Song, Cheng; Zeng, Fei; Pan, Feng
Abstract: Characteristics of one-port surface acoustic wave (SAW) resonators fabricated on ZnO/6H-SiC layered structure were investigated experimentally and theoretically. Phase velocities ( V p ), electromechanical coupling coefficients ( K 2 ), quality factors ( Q ), and temperature coefficients of frequency (TCF) of Rayleigh wave (0th mode) and first- and second-order Sezawa wave (1st and 2nd modes, respectively) for different piezoelectric film thickness-to-wavelength ( h ZnO /λ ) ratios were systematically studied. Results demonstrated that one-port SAW resonators fabricated on the ZnO/6H-SiC layered structure were promising for high-frequency SAW applications with moderate K 2 and TCF values. A high K 2 of 2.44% associated with a V p of 5182 m s −1 and a TCF of −41.8 ppm/°C was achieved at h ZnO /λ = 0.41 in the 1st mode, while a large V p of 7210 m s −1 with a K 2 of 0.19% and a TCF of −36.4 ppm/°C was obtained for h ZnO /λ = 0.31 in the 2nd mode. Besides, most of the parameters were reported for the first time and will be helpful for the future design and optimization of SAW devices fabricated on ZnO/6H-SiC layered structures.